Biflavonoids from the twigs and leaves of Cephalotaxus oliveri Mast. and their α-glucosidase inhibitory activity. Issue 12 (15th June 2022) - Song, Min; Xiao, Tong; Wu, Qiu-Shuang; Kwok, Hang Fai; Chan, Ging; Lin, Li-Gen; Zhang, Xiao-Qi; Ye, Wen-Cai; He, Sheng-Jiang; Zhang, Qing-Wen
Abstract: Three new biflavonoids, umcephabiovins C − E (1 − 3 ), along with fourteen known compounds were isolated from the twigs and leaves of Cephalotaxus oliveri . Their structures and configurations were elucidated by UV, IR, NMR, ECD, and HR-ESI-MS spectra. Compounds 1 − 3 exhibited significant α -glucosidase inhibitory activity with IC50 values of 7.05 ± 2.66, 24.45 ± 4.73, and 1.84 ± 1.14 μ M, respectively. Compound 11 showed moderate cytotoxicity against the BaF3/T315I cell line. Graphical Abstract: UF0001